Model based maximum power point tracking for satellite application - Lew, Jia Min (2017)
For a satellite, the primary power source is the solar energy. The amount of harvested solar energy will determine the depth of discharge of the battery in each orbit. This will in term decides the lifespan of the satellite. Hence, the ability to extract the maximum power from the Sun given any operating condition is important. In this thesis, perturb and observe (P&O) and incremental conductance (InC) maximum power point tracking (MPPT) methods have been studied for nano-satellites applications. There are two main operating scenarios of a satellite in space, namely the normal operation mode and safe-hold operation mode. The former is when the satellite is stabilized with its photovoltaic (PV) array pointing to the Sun. The latter is when the satellite experiences rotation and each PV array will face the Sun for a short period. From the simulation study, it is observed that the P&O and InC have inconsistent tracking performance with a reduced efficiency when the satellite is rotating. On the other hand, they have similar performance with efficiency up to 99% for normal operating scenario where the PV of satellite is facing towards the Sun. To overcome the shortcoming of poor tracking efficiency when the satellite is rotating, a new model based MPPT algorithm with solar insolation and maximum power point estimation (SIMPPE) concept is proposed. The SIMPPE algorithm uses voltage, current and temperature measurements incorporated into a single diode PV model to estimate the PV solar insolation level. This is then used to reconstruct the I-V curve and the estimate of maximum power point (MPP) voltage of the PV array. The simulation results show that the SIMPPE algorithm has a tracking efficiency of above 97% for all satellite operating scenarios. The hardware-in-the-loop test system with solar array simulators and electronic loads is used for experimental validation. In the experimental studies, the results show that the tracking efficiency for the SIMPPE algorithm has consistent tracking efficiency of 91% when the satellite is rotating. A temperature and MPP estimation (TMPPE) algorithm has been proposed to improve the SIMPPE algorithm by eliminating the PV temperature measurement to reduce number of sensor. The TMPPE algorithm uses four pairs of voltage and current measurements incorporated into a single diode PV model to estimate PV temperature and solar insolation simultaneously. The identified PV environmental conditions will then be used to reconstruct I-V curve and estimate MPP voltage. The simulation result shows that the TMPPE algorithm has improved tracking efficiency compared to conventional MPPT methods when the satellite is rotating. The TMPPE algorithm has been validated experimentally using hardware-in-the-loop test system. The experimental results show that the tracking efficiency for the TMPPE algorithm under normal operating and safe-hold operating scenarios are 94% and 87% respectively.